Barriers and Facilitators to Medicines Use in Patients With Vision Impairment: A Theory‐Informed Qualitative Study of Patients and Caregivers - Basma Y. Kentab; Heather E. Barry; Sinaa A. Al‐Aqeel; Carmel M. Hughes (Health Expectations)
ABSTRACT Introduction Previous studies have highlighted numerous challenges with medicines use for patients with vision impairment, but evidence is lacking on interventions to support safe and effective medicine use for this population. This study aimed to identify potential barriers/facilitators of medicines use from the viewpoint of patients/caregivers, to establish a theory‐informed foundation for a future intervention. Methods Semi‐structured interviews were conducted with patients with vision impairment and their caregivers in Saudi Arabia. Participants were recruited from low‐vision clinics and a non‐profit organisation. The Theoretical Domains Framework (TDF) informed the topic guide and served as the theoretical basis for examining participants' behaviours. Interviews explored the barriers/facilitators to obtaining and taking medicines (i.e. the target behaviours). Data were analysed using the framework method and content analysis. Key TDF domains were identified by assessing the relative frequency of themes, the existence of conflicting themes and the perceived theme impact on target behaviours. Results Twelve patient/caregiver dyads and 18 individual patients were interviewed. Patients' ages ranged from 19 to 88 years, with 21 females and 9 males. Patients/caregivers demonstrated good knowledge of medicines used, and resourcefulness in finding methods to manage medication use (Domains: ‘Knowledge’ and ‘Skills’). ‘Environmental context and resources (ECR)’ and ‘Social influences’ were the two most coded domains. Participants reported the usefulness of several resources including pill organisers and smartphones but described problems with pharmacy environments (Domain: ‘ECR’). Caregivers played a major role in assisting patients with medicines. Participants had some positive encounters with pharmacists but reported difficulties in discussing medication issues with them. Many participants had a narrow view of the pharmacist's role (Domain: ‘Social influences’). Maintaining a routine was a major facilitator under the ‘Memory, attention and decision processes’ and ‘Behavioural regulation’ domains. Six TDF domains were considered ‘key’ to participants' behaviours. Conclusions This study is the first to utilise a theoretical approach to understand the behaviour of patients with vision impairment in relation to medication use. It provides a comprehensive understanding of the role of caregivers and what influences their own behaviours. Findings will inform the future development of an intervention to support safe and effective medicine use for patients with vision impairment. Patient or Public Contribution An author met with an administrator at the ‘National Association of the Blind’ (Kafeef) in Riyadh to enhance the research team's understanding of vision impairment, and the practicality and logistics for identifying and recruiting patients. A draft of the interview guides was piloted with two patients and their caregivers and they were asked for feedback on the questions with amendments made accordingly.